2023
DOI: 10.1001/jamanetworkopen.2023.0147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjunctive Simvastatin on Depressive Symptoms Among Adults With Treatment-Resistant Depression

Abstract: ImportanceImmune-metabolic disturbances have been implicated in the pathophysiology of major depressive disorder and may be more prominent in individuals with treatment-resistant depression (TRD). Preliminary trials suggest that lipid-lowering agents, including statins, may be useful adjunctive treatments for major depressive disorder. However, no adequately powered clinical trials have assessed the antidepressant efficacy of these agents in TRD.ObjectiveTo assess the efficacy and tolerability of adjunctive si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The study characteristics are summarized in Table 1 . Of the seven included studies, all were completed and reported clinical outcomes ( 17 23 ). Six RCTs enrolled patients with MDD ( 17 20 , 22 , 23 ), while one enrolled patients with MDD or BD ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study characteristics are summarized in Table 1 . Of the seven included studies, all were completed and reported clinical outcomes ( 17 23 ). Six RCTs enrolled patients with MDD ( 17 20 , 22 , 23 ), while one enrolled patients with MDD or BD ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven included studies, all were completed and reported clinical outcomes ( 17 23 ). Six RCTs enrolled patients with MDD ( 17 20 , 22 , 23 ), while one enrolled patients with MDD or BD ( 21 ). One RCT enrolled patients with a history of coronary artery bypass surgery in the last 6 months ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations